Indirect costs of the Rheumatoid arthritis in Poland - Emilia Howoruszko; Szymon Szumiał; Aleksandra Izabela Czerw (Kazimierz Wielki University, 2019)
It is estimated that about 400,000 people in Poland suffer from rheumatoid arthritis (RA). Only a few epidemiological studies documenting the incidence of musculoskeletal disorders in the Polish population have been conducted. The medical literature mainly states that rheumatoid arthritis affects approximately 1% of the population and occurs 2-4 times more often in women than in men. RA is a disease that can develop at any age. In this group of diseases, indirect costs significantly exceed direct costs. Easier and more efficient access to rheumatology outpatient clinics would contribute to a quicker diagnosis of patients and, consequently, to reducing indirect costs of RA, and access to modern therapies would translate into a reduction of indirect costs related to rheumatoid arthritis. Results of studies conducted by other authors available in literature demonstrate that these diseases cause both an increased absence at work, i.e. missing days at work, and presenteeism, i.e. an increased ineffective presence at work due to ill-being. Indirect costs increase with increased disease activity. These costs can be significantly reduced through early diagnosis and introduction of effective treatment.